MAIN TYPES OF MINOR AND MEDIUM INNOVATIVE ENTEPRISES - A. G. Komissarov (Модернизация, инновация, развитие, 2016)
Conversion of Eastern Europe countries and RF to market economics causes many organizational, legal and infrastructural problems to rise. By the degree of «innovativeness», minor and medium enterprises are classified to three categories: «leader», «successor» and «outsider». Minor enterprises to whom different support may be extended by regional powers are grouped to 4 types.